Obstacles modelling reality: two exploratory studies on physics defined and undefined problems - Truyol, María Elena; Sanjosé López, Vicente; Gangoso, Zulma Estela (2022)
Fil: Truyol, María Elena. Universidad Nacional de Córdoba. Instituto de Física Enrique Gaviola; Argentina.